204k views
2 votes
If 2y^2+2=x^2, then find d^2y/dx^2 at the point (-2, -1) in simplest form.​

1 Answer

4 votes

Answer:


(d^2y)/(dx^2)_((-2, -1))=(1)/(2)

Explanation:

We have the equation:


2y^2+2=x^2

And we want to find d²y/dx² at the point (-2, -1).

So, let's take the derivative of both sides with respect to x:


(d)/(dx)[2y^2+2]=(d)/(dx)[x^2]

On the left, let's implicitly differentiate:


4y(dy)/(dx)=(d)/(dx)[x^2]

Differentiate normally on the left:


4y(dy)/(dx)=2x

Solve for the first derivative. Divide both sides by 4y:


(dy)/(dx)=(x)/(2y)

Now, let's take the derivative of both sides again:


(d)/(dx)[(dy)/(dx)]=(d)/(dx)[(x)/(2y)]

We will need to use the quotient rule:


(d)/(dx)[f/g]=(f'g-fg')/(g^2)

So:


(d^2y)/(dx^2)=((d)/(dx)[(x)](2y)-x(d)/(dx)[(2y)])/((2y)^2)

Differentiate:


(d^2y)/(dx^2)=((1)(2y)-x(2(dy)/(dx)))/(4y^2)

Simplify:


(d^2y)/(dx^2)=(2y-2x(dy)/(dx))/(4y^2)

Substitute x/2y for dy/dx. This yields:


(d^2y)/(dx^2)=(2y-2x(x)/(2y))/(4y^2)

Simplify:


(d^2y)/(dx^2)=(2y-(2x^2)/(2y))/(4y^2)

Simplify. Multiply both the numerator and denominator by 2y. So:


(d^2y)/(dx^2)=(4y^2-2x^2)/(8y^3)

Reduce. Therefore, our second derivative is:


(d^2y)/(dx^2)=(2y^2-x^2)/(4y^3)

We want to find the second derivative at the point (-2, -1).

So, let's substitute -2 for x and -1 for y. This yields:


(d^2y)/(dx^2)_((-2, -1))=(2(-1)^2-(-2)^2)/(4(-1)^3)

Evaluate:


(d^2y)/(dx^2)_((-2, -1))=(2(1)-(4))/(4(-1))

Multiply:


(d^2y)/(dx^2)_((-2, -1))=(2-4)/(-4)

Subtract:


(d^2y)/(dx^2)_((-2, -1))=(-2)/(-4)

Reduce. So, our answer is:


(d^2y)/(dx^2)_((-2, -1))=(1)/(2)

And we're done!

User ThienLD
by
4.8k points